Supreme Court, May 27, 2022: Placencia Delgado v Fisco - Soto Kloss, Eduardo (Derecho Público Iberoamericano, 2023)
Placencia Delgado with Fisco (Supreme Court, May 27, 2022, rol 131.095, justices Sergio Muñoz G., Angela Vivanco M., Adelita Ravanales A., Mario Carroza E. and member attorney Diego Munita I.) presents two useful issues to comment on, one of a procedural nature (statute of limitations) and the other, of constitutional and administrative law itself (the responsibility of the State Administration).